Neologisme Absurd dan Fungsi Fatis dalam Bahasa Brainrot di Budaya Digital TikTok Indonesia: Absurd Neologisms and Phatic Functions in Brainrot Language in Indonesian TikTok Digital Culture - Nurul Hidayah; Redika Cindra Reranta; Muhammad Iqbal Nasrulloh (Information Technology and Science(ITScience), 2026)
The Brainrot phenomenon on TikTok has produced absurd linguistic forms not found on other platforms. This study aims to map absurd neologisms and identify their phatic functions and roles in constructing group identity in the Indonesian TikTok community. A descriptive qualitative approach was used with content analysis of 50 TikTok videos hashtagged #Brainrot and related hashtags, from March to May 2026. Data were analyzed using an expanded neologistic framework that included the concept of absurd neologisms and Jakobson's theory of language function. The results reveal five categories of absurd neologisms: extreme clipping (rizz, gyatt), pseudo-reduplication (cupapi munianio, tung tung tung sahur), absurd composition (skibidi toilet, sigma boy), absurd onomatopoeia/interjections (hawk tuah, bomblacat), and new productive suffixes (-core, -maxxing). Phatic functions take five forms: explicit markers of group boundaries (IYKYK, moots), absurdity as an implicit marker of membership, meta-content (Brainrot quiz), hashtags as markers of affiliation, and phatic greetings and closings. In conclusion, absurd neologisms and phatic functions mutually reinforce group identity, with TikTok's affordances (short duration, audio dominance, and the YP algorithm) as the primary explanatory factor. These findings enrich the study of neology and phatic functions in short video-based digital communication.